The Value Of Justice In Dispute Resolution BAWASLU - Erniyanti Erniyanti; Febry Rizky Al Fadilla Sitompul; Ngatemi Ngatemi (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
Elections in Indonesia have experienced many obstacles, including money politics, data manipulation, deliberately eliminating other people's voting rights, deliberately providing untrue information about themselves or others about a matter required for filling out the voter list, determining the number of ballots printed exceeds the number determined by law, and so on, which causes election disputes. The settlement of legislative election disputes is resolved by Bawaslu, and if an election crime occurs, it will be forwarded to the police. In fact, in resolving disputes in the regional elections that occur, Bawaslu is still unable to accommodate the sense of justice of the parties to the dispute. Therefore, it is necessary and very important to reconstruct the substance, structure, and culture of the electoral management institution to resolve electoral disputes, especially the regional election, in order to produce a fair regional election (election of governors, rectors, and mayors).